Heat transfer characteristics of mixed-convection, couple-stress MHD ternary hybrid nanofluid flow past a stretching and shrinking surface with the impact of viscous dissipation - Rehman, Ali; Saad, Abdullah Aziz; İnç, Mustafa; Abas, Siti Sabariah Binti; Sudarmozhi, K. (Emerald Group Publishing Ltd, 2026)
PurposeThis study investigates the heat transfer and flow characteristics of mixed-convection, couple-stress magnetohydrodynamic (MHD) ternary hybrid nanofluid (THNF) flow over stretching and shrinking surfaces embedded in a porous medium. This study aims to understand the combined effects of viscous dissipation, magnetic field, buoyancy forces and nanoparticle dispersion on velocity, temperature, skin friction and heat transfer rates, with particular relevance to blood-based nanofluid systems.Design/methodology/approachA mathematical model is developed for two-dimensional, incompressible, laminar flow of a couple-stress THNF composed of Ag, multiwalled carbon nanotubes and single-walled carbon nanotubes nanoparticles dispersed in blood. The nonlinear governing partial differential equations are transformed into ordinary differential equations using similarity transformations. The resulting system is solved semi-numerically using the Homotopy analysis method (HAM) implemented through Mathematica packages BVPh 1.0 and BVPh 2.0. Parametric effects of key dimensionless numbers are analyzed graphically and numerically.FindingsThe results show that increasing magnetic and couple-stress parameters reduces velocity due to Lorentz force and microstructural resistance, while buoyancy and suction enhance fluid motion. Temperature increases with higher Eckert number, nanoparticle volume fraction and magnetic parameter due to viscous dissipation and Joule heating. Skin friction increases with mixed convection strength, whereas the Nusselt number rises with the Grashof number, indicating enhanced convective heat transfer.Originality/valueTo the best of the authors' knowledge, this work presents the first unified HAM-based analysis of mixed-convection, couple-stress MHD THNF flow over stretching and shrinking surfaces using a blood-based fluid. The findings provide valuable insights for the design of biomedical, microfluidic and thermally regulated MHD systems.
Keywords: Mixed-convection flow; MWCNT, SWCNT, Ag; Homotopy analysis method; MHD; Viscous dissipation